Analisis Potensi Pengembangan Agrowisata Berbasis Subak di Desa Baha, Kecamatan Mengwi, Kabupaten Badung - DWIPAYASA, I MADE; SUAMBA, I KETUT; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
PotentialAnalysis of Subak-Based Agro-turism Development in Baha Village, DistrictMengwi, Badung Regency Baha Village is one of the tourism village which is on developed in Badung Regency. The development of Baha Tourism Village is not developing well, as proven from the small number of the visitors. The problem is caused due to the lack of highlight of Bahas’ tourism products. Baha is need to develop it’s deversification on agrotourism therefore the study is needed. This study aimed (i) to find out the farmers’ perseption about agrotourism in subak area of Baha Village, (ii) to find out the requirements for fulfilled agro-tourism development in the subak area of Baha Village, and also (iii) to find out the potential for agro-tourism development in the subak area of Baha Village. Methods of data collection are interviews, questionnaires, and focus group discussions. The obtained data were analyzed using qualitative descriptive methods. The results of this study showed that farmers' perceptions on developing the potential of agro-tourism in the subak area of Baha Village were categorizing sufficient which achieve of 66.51% and the subak area in Baha Village which had not large potential to be developed as agrotourism due to the condition of the subak area of Baha Village. Its only supported by accessibility and infrastructure without any objects and attractive attractions and unique agrotouristic product as the main attraction. Some suggestions that researcher suggest are; (i) it is necessary from other parties in developing agrotourism in Baha Village including government institutions, academic institutions, and the private sector, (ii) further research is needed in developing agro-tourism in Baha Village such as research that examines agro-tourism development strategies.